Health-related quality of life of multiple myeloma patients after the first-line treatment: results of a prospective cohort study (Research, Society and Development, 2022)
Objective: The aim of this study was to evaluate whether there was an improvement or a deterioration of health-related quality of life (HRQoL) of multiple myeloma patients (MM), and to assess the associated factors with HRQoL after 12 months of treatment. Methods: We performed a prospective cohort study with MM patients in first-line treatment from public and private onco-hematology health services in a Brazilian metropolis. HRQoL, socio-demographic and clinical variables were obtained by interviews and review of medical charts. HRQoL and peripheral neuropathy (PN) were collected through validated instruments (QLQ-C30, QLQ-MY20, CINQ). Medians of the HRQoL scores, obtained at baseline and follow-up interviews, were compared. Median HRQOL scores at follow-up were compared by variables. The improvement or deterioration in HRQoL and the association with variables were measured. Results: Thirty-three patients completed the follow-up, with ISS III (25.0 %), on polypharmacy (72.2 %), using a thalidomide+bortezomib-based regimen as first-line (19.4 %), and median age of 66.5 years. HRQoL Summary score, Functioning, Symptom scales, and Future Perspective scores were improved between periods (p